Treatment of a patien twith chronic renal failure dialyzed with CAPD method hospitalized due to peritoneal infection. - Grączewska, Natalia (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2022)
One of the 21st century diseases is chronical renal failure. It includes many diseases which can be divided into primary like affecting only the kidneys and secondary, when kidney damage is the result of an ongoing systematic process. It consist of 5 stages that depends on degree of renal disfunction which is measured by the degree of glomerular filtration. Symptoms are different and depends on cause, which led to their damage. There are three treatments for chronic renal disease: hemodialysis, peritoneal dialysis, and kidney transplantation. Peritoneal dialysis should be the first method of dialysis therapy offered to patients with end-stage of renal disease because it allows residual diuresis to be maintained longer than hemodialysis, which is associated with less fluid and dietary restriction. The most common complication is dialysis peritonitis. Main symptoms are abdominal pain and clouding of the dialysis fluid. Recommended method of treatment is the introduction of intravenous and intraperitoneal antibiotics, which is associated with the hospitalization of the patient. Infectious complications in peritoneal dialysis have a significant impact on the quality of patients life, therefore nurses that caring on patients needs high professional knowledge and involvement in the patient education process on each of treatment stage.